Flexible Microstrip Antenna for Skin Contact Application - Sudhir Shrestha; Mangilal Agarwal; Parvin Ghane; Kody Varahramyan (International Journal of Antennas and Propagation, 2012)
Microstrip antennas are finding a growing medical application in imaging, diagnosis, and treatment. This paper presents a flexible microstrip antenna that can be placed in contact with the human skin. The developed antenna is only 0.25 mm thick, has 32 mm × 31 mm dimensions, and −19 dB measured |𝑆11| parameter at 2.45 GHz. A specific application of the antenna in microwave breast imaging is considered. Analytical results using simulation models and experimental results using skin phantoms are presented and discussed.